Chroma Color acquires Adam Gates & Company. Issue 8 (August 2021) - Unknown
Abstract : Chroma Color Corporation division Epolin, a manufacturer of near-infrared (NIR) absorbing dyes and thermoplastic compounds, has announced the acquisition of Adam Gates & Company LLC.